Prevalence, drug education, and other associated factors of current illicit drug use among a nationally representative sample of school-aged adolescents in the Philippines in 2019 - Supa Pengpid; Karl Peltzer; Lyndon Esconde Santos; Earl Francis Infante Mallari (Substance Abuse Treatment, Prevention, and Policy)
Abstract Background The aim of the study was to assess the prevalence, drug education, and associated individual level, family and peer level, school level and community/macro level risk/protective factors of current illicit drug use among in-school adolescents in the Philippines. Method The 2019 Philippines Global School-based Student Health Survey (GSHS), a nationally representative survey of teenagers aged 11 to 18 (mean age 13.8 years, Standard Deviation-SD = 1.5) that used a multistage sampling technique, provided the study’s data. Past 30-day illicit drug use, including cannabis, methamphetamine, ecstasy, rugby (a contact cement used as an adhesive which contains Toluene), and cocaine, was assessed by self-report. In order to determine the variables associated with current illicit drug use, the study used bivariate and multivariable logistic regression analysis. Results The proportion of current illicit drug use was 14.1%, 8.6% among girls and 19.1% among boys. In the final adjusted model in relation to individual level risk/protective factors found that male sex (Adjusted Odds Ratio-AOR = 1.81, 95% Confidence Interval-CI = 1.45–2.28), food insecurity (AOR = 1.58, 95% CI = 1.33–1.88), psychological distress (AOR = 1.40, 95% CI = 1.10–1.77), current alcohol use (AOR = 2.14, 95% CI = 1.81–2.51) were positively associated and older age (15–18 + years) (AOR = 0.59, 95% CI = 0.45–0.77) was negatively associated with current drug use. In terms of family and level factors, high parental support (AOR = 0.45, 95% CI = 0.32–0.63), having close friends (AOR = 0.55, 95% CI = 0.38–0.80) and peer support (AOR = 0.65, 95% CI = 0.51–0.81) were all negatively associated with current drug use. Regarding school level factors, having been taught where to get help for drug problems (AOR = 0.77, 95% CI = 0.62–0.94) was inversely associated and having been taught about drug problems was marginally significantly negatively associated with current drug use. Furthermore, school truancy (AOR = 1.80, 95% CI = 1.43–2.27) was positively associated with current drug use. Community/macro level factors found that participation in physical fighting (AOR = 1.56, 95% CI = 1.24–1.97), and “someone offered, sold, or given you a drug,” (AOR = 5.40, 95% CI = 4.42–6.74) were positively associated with current drug use. Conclusion One in seven Filipino adolescents engaged in current illicit drug use in 2019. Protective factors (such as high parental and peer support) and drug education were negatively associated with current illicit drug use. Individual and community level factors (such as psychological distress, exposure to drugs, alcohol use, and interpersonal violence) were positively associated with current illicit drug use. School and community programmes and policies may target to decrease psychosocial stressors, promote protective factors, and enhance curriculum-based drug education among adolescents in the Philippines.